AGAMA MENOLAK PATRIARKISME (Pendekataan Sosio-Teologis) - Aini, Adrika Fithrotul (Universitas Islam Negeri Raden Intan Lampung, 2015)
Gender issues became debated and isn’t a new thing in the community. The more rampant and the more legitimating the Gender’s construction becomes the more lasting the community’s understanding of the built construction will be. This paper will talk about a review of Inayah Rohmaniyah’s book entitled Konstruksi Patriarkhi dalam Tafsir Sebuah Agama Sebuah Jalan Panjang. This is a recent book covering about patriarchy’s construction happening around the community and want to understand the false legitimation to the people again, that the religion text’ is one of the thing encouraging the lasting patriarchy’s construction. The reconstruction of the religion text’ with the method is necessary to straighten back the disparaties religion text understanding. The sosio-theology-contextual approach is one of the contributions that will be given in this book.